Triatomines: Trypanosomatids, Bacteria, and Viruses Potential Vectors? - Vieira, Caroline Barreto; Praça, Yanna Reis; Bentes, Kaio Luís da Silva; Santiago, Paula Beatriz; Silva, Sofia Marcelino Martins; Silva, Gabriel dos Santos; Motta, Flávia Nader; Bastos, Izabela Marques Dourado; de Santana, Jaime Martins; de Araújo, Carla Nunes (Frontiers in Cellular and Infection Microbiology, 2018)
Triatominae bugs are the vectors of Chagas disease, a major concern to public health especially in Latin America, where vector-borne Chagas disease has undergone resurgence due mainly to diminished triatomine control in many endemic municipalities. Although the majority of Triatominae species occurs in the Americas, species belonging to the genus Linshcosteus occur in India, and species belonging to the Triatoma rubrofasciata complex have been also identified in Africa, the Middle East, South-East Asia and in the Western Pacific. Not all of Triatominae species have been found to be infected with Trypanosoma cruzi, but the possibility of establishing vector transmission to areas where Chagas disease was previously non-endemic has increased with global population mobility. Additionally, the worldwide distribution of triatomines is concerning, as they are able to enter in contact and harbor other pathogens, leading us to wonder if they would have competence and capacity to transmit them to humans during the bite or after successful blood feeding, spreading other infectious diseases. In this review, we searched the literature for infectious agents transmitted to humans by Triatominae. There are reports suggesting that triatomines may be competent vectors for pathogens such as Serratia marcescens, Bartonella and Mycobacterium leprae, and that triatomine infection with other microrganisms may interfere with triatomine-T. cruzi interactions, altering their competence and possibly their capacity to transmit Chagas disease.